(untitled) (Theatrum historiae, 2016)
The paper sets a goal to clarify, by the form of a case study into the destiny of the three generations of the native French family of the Raduits, the connection between the economic resources, which the mentioned family could gain and mobilize, and the economic and financial aspects of army service. They were not only the inherent part of aristocratic warrior careers, but they also, in the situation of yet undeveloped fiscal mechanisms of a premodern state that was still searching for ways how to finance its permanent army, represented a risk factor which, to a considerable extent, decided about success or failure not only of the particular individuals, but as well their families and other generations of the dynasty, in the strictly socially stratified society of the early modern period.